Страх (Тридцать пятый и другие годы) - Рыбаков Анатолий Наумович (Читать [модно], 2004)
Экземпляры: Аб (20110801) / Инвентарный номер: 97488 / Цена: 100.00 / Авт.знак: Р 93 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6